The Pediatric Toronto Extremity Salvage Score (pTESS): Validation of a Self-reported Functional Outcomes Tool for Children with Extremity Tumors. Issue 9 (September 2019) - Piscione, Janine; Barden, Wendy; Barry, Janie; Malkin, Alexandra; Roy, Trisha; Sueyoshi, Tyki; Mazil, Karen; Salomon, Steven; Dandachli, Firas; Griffin, Anthony; Saint-Yves, Hugo; Giuliano, Pina; et al.
Abstract: Background: The physical function of children with sarcoma after surgery has not been studied explicitly. This paucity of research is partly because of the lack of a sufficiently sensitive pediatric functional measure. The goal of this study was to establish and validate a standardized measure of physical function in pediatric patients with extremity tumors. Questions/purposes: (1) What is the best format and content for new upper- and lower-extremity measures of physical function in the pediatric population? (2) Do the new measures exhibit floor and/or ceiling effects, internal consistency, and test-retest reliability? (3) Are the new measures valid? Methods: In Phase 1, interviews with 17 consecutive children and adolescents with bone tumors were conducted to modify the format and content of draft versions of the pediatric Toronto Extremity Salvage Score (pTESS). In Phase 2, the pTESS was formally translated into French. In Phase 3, 122 participants between 7 and 17.9 years old with malignant or benign-aggressive bone tumors completed the limb-specific measure on two occasions. Older adolescents also completed the adult TESS. Floor and ceiling effects, internal consistency, test-retest reliability, and validity were evaluated. Results: Feedback from interviews resulted in the removal, addition, and modification of draft items, and the pTESS-Leg and pTESS-Arm questionnaires were finalized. Both versions exhibited no floor or ceiling effects and high internal consistency (α > 0.92). The test-retest reliability was excellent for the pTESS-Leg (intraclass correlation coefficient [ICC] = 0.94; 95% CI, 0.90-0.97) and good for the pTESS-Arm (ICC = 0.86; 95% CI, 0.61-0.96). Known-group validity (ability to discriminate between groups) was demonstrated by lower mean pTESS-Leg scores for participants using gait aids or braces (mean = 68; SD = 21) than for those who did not (mean = 87; SD = 11; p < 0.001). There was no significant difference between pTESS arm scores among respondents using a brace (n = 5; mean = 73; SD = 11) and those without (n = 22; mean = 83; SD = 19; p = 0.13). To evaluate construct validity, we tested a priori hypotheses. The duration since chemotherapy correlated moderately with higher pTESS-Leg scores (r = 0.4; p < 0.001) but not with pTESS-Arm scores (r = 0.1; p = 0.80), and the duration since tumor resection correlated moderately with higher pTESS-Leg scores (r = 0.4; p < 0.001) but not pTESS-Arm scores (r = 0.2; p = 0.4). Higher VAS scores (that is, it was harder to do things) antecorrelated with both pTESS versions (pTESS-Leg: r = -0.7; p < 0.001; pTESS-Arm: r = -0.8; p < 0.001). To assess criterion validity, we compared the pTESS with the current "gold standard" (adult TESS). Among adolescents, strong correlations were observed between the TESS and pTESS-Leg (r = 0.97, p < 0.001) and pTESS-Arm (r = 0.9, p = 0.007). Conclusions: Both pTESS versions exhibited no floor or ceiling effects and had high internal consistency. The pTESS-Leg demonstrated excellent reliability and validity, and the pTESS-Arm demonstrated good reliability and reasonable validity. The pTESS is recommended for cross-sectional evaluation of self-reported physical function in pediatric patients with bone tumors. Level of Evidence: Level II, outcome measurement development.